2008
DOI: 10.1104/pp.108.128231
|View full text |Cite
|
Sign up to set email alerts
|

RETARDED PALEA1 Controls Palea Development and Floral Zygomorphy in Rice  

Abstract: Poaceae, one of the largest flowering plant families in angiosperms, evolved distinct inflorescence and flower morphology diverging from eudicots and other monocots. However, the mechanism underlying the specification of flower morphology in grasses remains unclear. Here we show that floral zygomorphy along the lemma-palea axis in rice (Oryza sativa) is partially or indirectly determined by the CYCLOIDEA (CYC)-like homolog RETARDED PALEA1 (REP1), which regulates palea identity and development. The REP1 gene is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
159
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(167 citation statements)
references
References 49 publications
5
159
1
2
Order By: Relevance
“…The rep1 mutant displays retarded palea development with five vascular bundles at least partially affecting the floral bilateral asymmetric morphology. This finding therefore extends the function of the TCP gene family members in defining the diversification of floral morphology in grasses, and suggests that a common conserved mechanism controlling floral zygomorphy by CYC-like genes exists in both eudicots and monocots [32]. In addition, the palealess mutant (pal) with two leafy structures instead of the palea has been identified [49], suggesting that PAL1 is another key regulator of palea development in rice.…”
Section: Osmads6 Plays An Important Role In Specifying Rice Palea Idementioning
confidence: 79%
See 2 more Smart Citations
“…The rep1 mutant displays retarded palea development with five vascular bundles at least partially affecting the floral bilateral asymmetric morphology. This finding therefore extends the function of the TCP gene family members in defining the diversification of floral morphology in grasses, and suggests that a common conserved mechanism controlling floral zygomorphy by CYC-like genes exists in both eudicots and monocots [32]. In addition, the palealess mutant (pal) with two leafy structures instead of the palea has been identified [49], suggesting that PAL1 is another key regulator of palea development in rice.…”
Section: Osmads6 Plays An Important Role In Specifying Rice Palea Idementioning
confidence: 79%
“…We have recently shown that the CY-CLOIDEA (CYC)-like factor, RETARDED PALEA1 (REP1), is able to regulate palea identity and floral asymmetry in rice [32]. The REP1 gene is only expressed in palea primordium during early flower development [32].…”
Section: Osmads6 Plays An Important Role In Specifying Rice Palea Idementioning
confidence: 99%
See 1 more Smart Citation
“…To obtain the full-length cDNA of PTC1, RACE-PCR was performed with the GeneRacer kit (Invitrogen) as described before (Yuan et al, 2009). The PTC1 cDNA was amplified using 2 mL of RACE product from rice anther RNAs (stage 9) with Phusion hot-start high-fidelity polymerase (New England Biolabs).…”
Section: Isolation Of Ptc1 Full-length Cdnamentioning
confidence: 99%
“…However, the CYCLO-IDEA (CYC)-like homolog RETARDED PALEA1 (REP1) in rice is a palea-specific gene that plays essential roles in palea initiation by regulating cell proliferation and expansion but does not affect lemma development (Yuan et al, 2009). In the rep1 mutant, palea development is delayed and the palea morphology is also altered.…”
Section: Agl6-like Genes Are Markers For the Palea In Grassesmentioning
confidence: 99%